2016
DOI: 10.11648/j.ejcbs.20160206.16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Susceptibility Patterns of Methicillin Resistant Staphylococcus Aureus in Patients Attending the Laquintinie Hospital Douala, Cameroon

Abstract: Methicillin Resistant Staphylococcus aureus (MRSA) is a major health problem worldwide. Diseases caused by these microorganisms most often are difficult to treat consequently, present with severe outcomes. Despite the increase association of MRSA in most hospital acquired infections, surveillance systems to control the spread of these infections are lacking especially in the developing countries. The present study is part of a major study developed to trail the incidence of multidrug resistant pathogens in cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
5
14
0
Order By: Relevance
“…The mechanism of resistance to glycopeptides is not well defined, but it is suggested that resistance could be through the acquisition of the mobile genetic elements of vancomycin-resistant Enterococcus that cause changes in the metabolism and cell wall of Staphylococcus [38]. These results are in line with reports from previous studies on animal and clinical samples [22,33,39,40]. Ateba and colleagues recorded a moderate to high percentage (39-100%) of resistance to methicillin, ampicillin, penicillin G, sulfamethoxazole, oxytetracycline, and erythromycin among S. aureus isolates from communal farms [22].…”
Section: Discussionsupporting
confidence: 85%
“…The mechanism of resistance to glycopeptides is not well defined, but it is suggested that resistance could be through the acquisition of the mobile genetic elements of vancomycin-resistant Enterococcus that cause changes in the metabolism and cell wall of Staphylococcus [38]. These results are in line with reports from previous studies on animal and clinical samples [22,33,39,40]. Ateba and colleagues recorded a moderate to high percentage (39-100%) of resistance to methicillin, ampicillin, penicillin G, sulfamethoxazole, oxytetracycline, and erythromycin among S. aureus isolates from communal farms [22].…”
Section: Discussionsupporting
confidence: 85%
“…Finally, 24 studies were included in our review and met the criteria for MRSA proportions, genetic diversity, and antimicrobial resistance patterns in Cameroon [13,. Among the included studies, there were 22 studies on human MRSA epidemiology [13,[20][21][22][23][24][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], one study on animal epidemiology [25], two studies on food epidemiology [19,21], one study on environmental epidemiology [38].…”
Section: Study Selectionmentioning
confidence: 99%
“…Of the 24 studies included, 8 were conducted in the Central Region (33.3%) [13,22,24,27,37], and Five in the Western Region (20.8%) [30,32,35,36]. The Littoral (8.3%) [20,41] and South West (8.3%) regions [21,38] were studied twice each, while one study covered the Centre, Littoral, and South West regions (4.1%) [26]. In addition, one study included the Central and Southwest regions (4.1%) [39], and another focused on the Northwest and Southwest regions (4.1%) [19].…”
Section: Studies Characteristics Of the Epidemiology Of Mrsa In Cameroonmentioning
confidence: 99%
See 2 more Smart Citations